Obstetrical nursing: discovering advantages and difficulties faced by specialists in this area: DOI: 10.15343/0104-7809.200832.4.7 - Gonçalves Barbosa, Priscila (2008)
This is a descriptive-exploratory field research with a quantitative approach developed with 33 obstetric nurses who work inhealth and teaching institutions, public and private, located in Sao Paulo State. The study aimed to identify advantages and difficultiesfaced by obstetric nurse in their different work areas. Results showed that they most nurses graduated more than 5 years ago and workin Obstetrics for more than 7 years now; 39.4% work in public institutions and 21.2% in both public and private institutions. As forchildbirth assistance, they carry out 54.5% of them, and 56% of them carries out from 1 to 10 per week childbirths. It was also noticedthat most obstetricians (79%) have no difficulties in their work as a whole and they report advantages such as the possibility of educatingpregnant women and recent mothers, broad work opportunities, team work and the legal support provided by the specialization. Onlysix (18%) said to have work difficulties, and those pointed out the lack of technical ability. 33.4% spoke about the lack of autonomyand preconceptions by the medical team. The research allowed a reflection on the activities and contentment of obstetric nurses, who,even with some difficulties in their work, feel happy and believes that the advantages surpass by far the obstacles found in the area.